2016
DOI: 10.1002/j.0022-0337.2016.80.2.tb06074.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning Shade Differentiation Using Toothguide Trainer and Toothguide Training Box: A Longitudinal Study with Dental Students

Abstract: The positive training effect achieved with the Toothguide Training Box (TTB) has been demonstrated in previous studies. The aim of this study was to investigate the training effect with the TTB at six and 12 months using standardized color tests. The study involved 101 dental students. The participants were divided into two study groups and one control group. Ten standard color samples were determined under uniform environmental conditions with VITA 3D-Master. The control group (N=30) took the color test after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 36 publications
2
21
0
3
Order By: Relevance
“…Those identified as having average or poor color discrimination may desire to improve their shade‐matching ability through targeted training and exercises. Toothguide Trainer (Vita) and Tooth Training Box (Vita) are a few available software programs shown to have improved dental shade matching …”
Section: Discussionmentioning
confidence: 99%
“…Those identified as having average or poor color discrimination may desire to improve their shade‐matching ability through targeted training and exercises. Toothguide Trainer (Vita) and Tooth Training Box (Vita) are a few available software programs shown to have improved dental shade matching …”
Section: Discussionmentioning
confidence: 99%
“…The used shade guide (3D-Master, VITA Zahnfabrik) uses the same parameters for tooth color determination. All participants were tested with Color Vision Deficiency Test (CVD) using a beamer projection of the Ishihara test charts, before starting the test [26] The Toothguide-Training-Box (TTB, VITA Zahnfabrik, Figure 1) performs color matching under reproducible conditions, designed by Jakstat in 2002 and later improved in 2007 [13] . The tooth-shaped shade tabs were presented in the field of view in neutral grey background (reference).…”
Section: Methodsmentioning
confidence: 99%
“…Both further steps, the determination of chroma and hue, reduce color-matching errors with a compliance of almost 70% [6,8] . Clinical studies have demonstrated that the subjective color determination independent of the used color scale, but -in fact -gender-dependent can be learned [9,[10][11][12][13][14] . In their research with 614 participants of 15 universities in 9 countries, Haddad et al came to the conclusion that female achieved better in color determination results than male [11] and contradicts to Della Bona et al [15] who had assumed that only experience was the deciding factor in color determination.…”
Section: Methodsmentioning
confidence: 99%
“…Many researches have investigated the effectiveness of TTB as a method of color training. A positive effect has been linked to training that uses the TT and the TTB . In a recent study, the TTB quickly led to an improvement in tooth color differentiation among students.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the TTB quickly led to an improvement in tooth color differentiation among students. However, after 6 months, there was a decrease in the training effect . Shade‐matching performance may be a problematic even among dental practitioners.…”
Section: Introductionmentioning
confidence: 99%